Using the endowment effect to explain managerial resistance towards codetermination: Implications for employment relations from the German case. (18th October 2019) - Harcourt, Mark; Gall, Gregor; Wilkinson, Adrian; Croucher, Richard; Lam, Helen
Abstract: This article provides an innovative defence of codetermination by way of exploring two of the most significant theorised objections to it from neo‐liberal and libertarian perspectives, namely the defence of the right to manage as freely chosen by employees and employers alike, and the right to manage being the most efficient, lowest transaction cost mode of employee governance. Instead, we focus upon management preference emanating from the endowment effect, and manifested in management style and ideology, as a more credible explanation for management's support for its prerogative to manage. The endowment effect prompts both strong employer and manager objections to codetermination and weak employee willingness to seek it because humans place more value upon items currently in their possession than upon those they do not possess. We explore this argument by examining the experience of codetermination in Germany. The significance of our argument lies in identifying managerial preference as the key variable to be challenged and changed in order to pacify management opposition to codetermination through political, ideological, and institutional means.